On some controversially-discussed Raman and IR bands of beryl - Huong, Le Thi Thu; Häger, Tobias (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract. Natural and synthetic beryl, Al 2 Be 3 Si 6 O 18 , from various deposits and manufacturers were investigated with Raman, IR spectroscopy, Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) and Electron Microprobe Analysis (EMPA). The Raman-band at 1067-1072 cm -1 and the IR-band at 1071-1207 cm -1 have been assigned till now either to Si-O or to Be-O by different studies. Following the findings in this study that the position and Full Width at Half Maximum (FWHM) of these bands were related to the concentration of silicon but not that of beryllium, it stated that  these bands were generated by the vibration of Si-O. Keywords: Raman, Infrared spectroscopy, FWHM, band position, beryl.